Generating waist area-dependent ground reaction forces for long-duration spaceflight. (30th March 2021) - Ashari, Neeki; Kong, Mitchell; Poudel, Alisha; Friend, James; Hargens, Alan R.
Abstract: Prolonged microgravity exposure greatly weakens the bones and muscles of astronauts. This is a critical biomechanical issue for astronauts as they may be more prone to bone fractures. To combat this issue, lower body negative pressure (LBNP) is a concept that generates artificial gravitational forces that may help strengthen bones and muscles during long-term spaceflight. Negative pressure, defined as below ambient pressure, is applied within a chamber that encompasses the lower half of the body. By increasing the negative pressure, more ground reaction forces (GRFs) are generated beneath the subject's feet. We hypothesize that increasing the cross-sectional area (CSA) of the subject's waist will generate greater GRFs beneath the subject's feet. Six healthy subjects volunteered to participate under two different experimental conditions: 1) original CSA of their waist and 2) larger CSA of their waist. In both conditions the subjects were suspended in a supine position (simulated microgravity) along with a weight scale beneath their feet. Negative pressures ranged from zero to 50 mmHg, increasing in increments of 5 mmHg. At −50 mmHg, original CSAs generated 1.18 ± 0.31 (mean ± SD) of their normal bodyweight. Subjects generated about one bodyweight at −45 mmHg using their original waist CSA. At −50 mmHg, larger CSAs generated 1.46 ± 0.31 of their normal bodyweight. Subjects generated about one bodyweight at −35 mmHg using their larger waist CSA. These data support our hypothesis. This novel technique may apply less stress to the cardiovascular system and conserve power for exercise in the spacecraft.